IDENTIFIKASI TOMATO INFECTIOUS CHLOROSIS VIRUS PENYEBAB PENYAKIT KLOROSIS PADA TANAMAN TOMAT DI CIPANAS JAWA BARAT MELALUI PERUNUTAN NUKLEOTIDA GEN PROTEIN SELUBUNG UTAMA - Fitrianingrum Kurniawati; Gede Suastika; Giyanto . (Universitas Lampung, 2015)
Identification of tomato infectious chlorosis virus, the causal agent of chlorosis disease on tomato in Cipanas West Java by sequencing of main coat protein gene nucleotide. Tomato infectious chlorosis virus (TICV) causes chlorosis on tomato. Tomatoes infected by this virus shows interveinal yellowing, necrotic, bronzing, brittleness, and declining in productivity. This study aims to identify the causal agent of chlorotic disease on tomato by sequencing the coat protein gene. The methods involve collecting infected plants, total RNA extraction, cDNA synthesis, DNA amplification, visualization of the results of reverse transcription polymerase chain reaction (PCR), and phylogenetic analysis using BLAST, clustal w, Bioedit v 7.0.5.3, MEGA v 6:06. RT-PCR using spesific primers (CP-F TICV Bam and TICV R-Hind) amplified a DNA band of 792 bp, which has been successfully sequenced and identified as TICV. Nucleotide sequences homology analysis showed that TICV Indonesia_TWJ isolate Cipanas is the same strain as TICV from other countries (99.4 – 100%), such as Spain, Greece, USA, France, and Italy.